2014
DOI: 10.4236/wja.2014.41011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in HIV-Infected Cameroonian Patients

Abstract: Aims: Metabolic complications related to antiretroviral therapy are rarely investigated among HIV-infected patients in Cameroon. The study reports the prevalence of metabolic syndrome and its individual components among HIV-infected Cameroonians. Materials and Methods: We conducted a prospective, cross-sectional study of the prevalence of metabolic syndrome among 492 patients (338 women, 117 men; age range 20 years) recruited at a reference centre, the day hospital, Central Hospital in Yaounde between Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
15
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 22 publications
11
15
1
6
Order By: Relevance
“…The three most represented components of MS in our series were abdominal obesity, followed by HCH, HBP. Contrary to the data in the literature, where the dominant trio of the MS components are HTG, HCH and HBP [14] [16] [18], HTG is the component least represented in our study behind hyperglycemia whether the patient is exposed to HAART or naive. This low prevalence of HTG confirms a previous study that estimated HTG as the least frequent dyslipidemia among PLWHIV on HAART in the same proportions in Togo [11].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The three most represented components of MS in our series were abdominal obesity, followed by HCH, HBP. Contrary to the data in the literature, where the dominant trio of the MS components are HTG, HCH and HBP [14] [16] [18], HTG is the component least represented in our study behind hyperglycemia whether the patient is exposed to HAART or naive. This low prevalence of HTG confirms a previous study that estimated HTG as the least frequent dyslipidemia among PLWHIV on HAART in the same proportions in Togo [11].…”
Section: Discussioncontrasting
confidence: 99%
“…This low prevalence of HTG confirms a previous study that estimated HTG as the least frequent dyslipidemia among PLWHIV on HAART in the same proportions in Togo [11]. Tiozzo [18]. In Ethiopia, Tesfaye et al found the same result for women, but found no significant difference between the frequencies of hypertension compared to the two sexes [26].…”
Section: Discussionsupporting
confidence: 84%
“…From 602 records identified through electronic database searching, 19 records from cross‐references, and 28 417 records from the WHO International Clinical Trials Registry Platform, we excluded 560 abstracts and 11 duplicate records. Of 50 remaining full texts assessed for eligibility, 9 articles were withdrawn, leaving 41 studies that were deemed eligible for inclusion in the meta‐analyses . In total, there were 20 178 participants, with approximately twice as many ART‐exposed as there were ART‐naïve patients.…”
Section: Resultsmentioning
confidence: 99%
“…The average age of the total study population was 42 years, and women accounted for 40%. Most studies were conducted in low-and middle-income countries, including Brazil, 19,40,41,59 Cameroon, 39,42,51,57 Ethiopia, 20,30,54 Ghana, 56 India, 33,49,52,53,60 Nigeria, 32,38,55 South Africa, 17,31 Sri Lanka, 61 Thailand, 14 and Zambia. 46 However, the studies conducted in high-income countries were generally larger in size, comprising more than half of the total study population.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…A total of 573 abstracts and 17 full texts, including seven duplicate records, were excluded, leaving 39 eligible observational studies. [5][6][7][8]15,16, Thirty of these included studies were cross-sectional surveys, 5,16,[18][19][20][21][22][23][24][25][26]28,[31][32][33][34][35][36][37][39][40][41][42][44][45][46]48,49 whereas the other nine were cohort studies. A total of 44 903 HIV-infected patients (28% females) from 21 countries were included in our analyses, with significantly more study participants from high-income countries compared with low-and middle-income countries (89% versus 11%).…”
Section: Discussionmentioning
confidence: 99%